The rights of man - Paine, Thomas (Dover Publications, 1999)
One of Paine's greatest and most widely read works, considered a classic statement of faith in democracy and egalitarianism, defends the early events of the French Revolution, supports social security for workers, public employment for those in need of work, abolition of laws limiting wages, and other social reforms.
Keywords: Human Rights